Laser melting of groove defect repair on high thermal conductivity steel (HTCS-150) - B., Norhafzan; S. N., Aqida; F., Fazliana; Mohamed Reza Zalani, Mohamed Suffian; I., Ismail; C.M., Khairil (Springer Berlin Heidelberg, 2018)
This paper presents laser melting repair of groove defect on HTCS-150 surface using Nd:YAG laser system. Laser melting process was conducted using JK300HPS Nd:YAG twin lamp laser source with 1064 nm wavelength and pulsed mode. The parameters are pulse repetition frequency (PRF) that is set from 70 to 100 Hz, average power (PA) of 50–70 W, and laser spot size of 0.7 mm. HTCS-150 samples were prepared with groove dimension of 0.3 mm width and depths of 0.5 mm using EDM wire cut. Groove defect repaired using laser melting process on groove surface area with various parameters’ process. The melted surface within the groove was characterized for subsurface hardness profile, roughness, phase identification, chemical composition, and metallographic study. The roughness analysis indicates high PRF at large spot size caused high surface roughness and low surface hardness. Grain refinement of repaired layer was analyzed within the groove as a result of rapid heating and cooling. The hardness properties of modified HTCS inside the groove and the bulk surface increased two times from as received HTCS due to grain refinement which is in agreement with Hall–Petch equation. These findings are significant to parameter design of die repair for optimum surface integrity and potential for repairing crack depth and width of less than 0.5 and 0.3 mm, respectively.